(untitled) (Fiep Bulletin - online, 2011)
This is a study of literature review that aims to check on the databases SciELO, Lilacs, Pub Med and Highwire Press, publications about the effectiveness of the use of Unna Boot on the healing of venous ulcers. To do this, were used as descriptors the terms treatment of ulcers varicose and unna boot in the databases and Lilacs and Scielo unna boot in PubMed and HighWire Press. The inclusion criteria adopted for the selection articles were: work related to the effectiveness of Boot Unna in healing of UV; be presented in full text, are available online, open access, and have been published since 2000. Accordingly, were selected articles about clinical trials and literature review, and found that the use of Unna Boot is effective in healing UVs, although this therapy to be still undervalued.